2005
DOI: 10.1126/science.1112462
|View full text |Cite
|
Sign up to set email alerts
|

Periodically Triggered Seismicity at Mount Wrangell, Alaska, After the Sumatra Earthquake

Abstract: As surface waves from the 26 December 2004 earthquake in Sumatra swept across Alaska, they triggered an 11-minute swarm of 14 local earthquakes near Mount Wrangell, almost 11,000 kilometers away. Earthquakes occurred at intervals of 20 to 30 seconds, in phase with the largest positive vertical ground displacements during the Rayleigh surface waves. We were able to observe this correlation because of the combination of unusually long surface waves and seismic stations near the local earthquakes. This phase of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(118 citation statements)
references
References 13 publications
4
110
2
1
Order By: Relevance
“…S6c), near the Klutlan Glacier terminus, where there is also a historical record of shallow (< 10 km depth) seismicity and regional events flagged as glacial events by Alaska Earthquake Center analysts (West, 2014). Because of the poor data quality, it is difficult to distinguish whether the sources are icequakes similar to those observed in Antarctica triggered by the M w 8.8 Chile earthquake (Peng et al, 2014) or shallow earthquakes like those triggered near active volcanoes or geothermal regions (Prejean et al, 2004;West et al, 2005). Deducing which type of events actually occurred-icequakes or shallow earthquakes-would require more stations in the region.…”
Section: Discussionmentioning
confidence: 99%
“…S6c), near the Klutlan Glacier terminus, where there is also a historical record of shallow (< 10 km depth) seismicity and regional events flagged as glacial events by Alaska Earthquake Center analysts (West, 2014). Because of the poor data quality, it is difficult to distinguish whether the sources are icequakes similar to those observed in Antarctica triggered by the M w 8.8 Chile earthquake (Peng et al, 2014) or shallow earthquakes like those triggered near active volcanoes or geothermal regions (Prejean et al, 2004;West et al, 2005). Deducing which type of events actually occurred-icequakes or shallow earthquakes-would require more stations in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of a clear hydrologic connection, triggered earthquakes by large (M > 9) earthquakes may be global (e.g., West et al 2005;Velasco et al 2008). Anti-triggering, that is suppression of small earthquakes, may also occur (Okubo & Wolfe 2008).…”
Section: The Seismic Energy Density: a General Metricmentioning
confidence: 99%
“…Previously, it has been observed that some small earthquakes or tremors were triggered by the surface waves of a distant earthquake, particularly around volcanic or geothermal areas (Hill et al 1993;Gomberg 1996;Gomberg et al 2001Gomberg et al , 2004Hough and Kanamori 2002;Husen et al 2004;Prejean 2004;West 2005;Hill and Prejean 2007;Peng and Chao 2008;Peng et al 2011;Wu et al 2011). The peak dynamic stresses carried by large surface waves greater than ~0.1 bar (~0.01 MPa) are capable of triggering micro-earthquakes or tremors at remote distances as far as 10000 km (Hill and Prejean 2007).…”
Section: Introductionmentioning
confidence: 99%